Professional Development for Library Interns: Creation of a Guide and Program - Hedreen, Rebecca; Bernier, Jessica; Haakonsen, Alexis; Mottolese, Jennifer; Tiu, Ariss (Journal of Graduate Librarianship, 2024)
Keywords: dept.lib

Developing resilient leaders: a training for students - Jansen, Amy L.; Wieland, Alice (Journal of Leadership Education, 2024)
This assignment is designed to enhance resilience among students in leadership courses. It leverages the US Army’s Master Resilience Training (MRT) framework and positive psychology to develop resiliency skills.A three-part experiential workshop integrates academic readings (providing a foundation of resilience concepts), explores the influence of personal identities on leadership and connects leadership skills with resilience concepts.Participants reflect on self-awareness tools and positive psychology and create personalized action plans. Participants' resilience skills are enhanced with their personalized resiliency plan.The program provides a structured approach to resilience training, which can be integrated into university curriculums. Students gain self-awareness and psychological tools to manage challenges, which are valuable for personal growth and professional development. There is a persistent gender gap in leadership, and for women to attain greater parity in leadership positions, resilience skills are imperative. By focusing on identity-related factors, the program prepares future leaders for challenges in attaining leadership positions.This program is uniquely tailored for students aspiring to leadership positions, with an emphasis on the role of identity, such as gender, in leader emergence and overcoming related challenges.
Keywords: dept.lib; peer-reviewed

The interplay of power, incentives, academic freedom, and gender equity - Wieland, Alice; Jansen, Amy (Journal of Academic Freedom, 2024)
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.
Keywords: dept.lib; dept.mgt